Music Makes Me : Fred Astaire and Jazz - Decker, Todd R. (Book collections on Project MUSE., 2011)
Fred Astaire is best known for his brilliant dancing in the movie musicals of the 1930s, but in Music Makes Me, Todd Decker argues that Astaire's work as a dancer and choreographer, particularly in the realm of tap dancing, made a significant contribution to the art of jazz.